Processo de ensilagem de sobras da cultura do repolho na alimentação animal - SILVA, M. R. M.;SILVA, MAX ROSSI MACHADO DA (2014)
The objective of this research was to evaluate the chemical composition, the fermentation and aerobic stability profile of cabbage treated silages with ground corn inoculated or not Wirth BAL. the treatments evaluated were: cabbage silage with 200, 300, 400, 500 and 600 g/kg of ground corn (based on fresh material), associated or not to application of bacterial inoculant. The experiment was conducted at the Faculty of Agronomy of the University José do Rosário Vellano-UNIFENAS, Campus de Alfenas-MG organized in a factorial scheme 5x2 and driven in a completely randomized design, with four replicates. We used experimental silos made of PVC pipes with a capacity of 4 L of forages. The chemical composition, differences between forage and silage, fermentative profile, IVDMD coefficients and maximum pH data were analyzed with a mixed model using the PROC mixed of SAS (v 9.2), considering level of corn meal and inoculant as fixed effects and the residual error as a random effect. As expected, corn meal addition increased the DM content of cabbage silages, observing higher values for the highest level of addition. Conversely, CP, aNDF, ADF and lignin contents decreased with corn meal addition. Because the considerable reduction on the aNDF content, the IVDMD coefficients slight increased (P < 0.10), but all cabbage silages showed digestibility higher than 740 g/kg of DM. Relative to fermentative process, the pH values of cabbage silages linearly increased due to high levels of corn meal addition. Cabbage ensiled with 200 and 300 g/kg of corn meal had high ammonia N production, and the inoculant also increased the ammonia N concentration in these levels. Similarly, cabbage silages treated with low amount of corn meal (200 and 300 g/kg) showed great effluent and gas losses, where, insofar corn meal was added, fermentative losses decreased. Overall, cabbage silages treated with 600 g/kg of corn meal had lower maximum pH during aerobic exposure, but all silages had the same aerobic stability (12 h). The ensiling of cabbage is possible, but we recommended to apply 400 g/kg of corn meal to improve the silage quality, whereas the use of inoculant is unnecessary.